(1)x—1/2=2x+1/6—1(2)2m+1/3的相反数=2—5m—1/4(2m+1/3)的相反数=2—5m—1/4
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 03:16:26
(1)x—1/2=2x+1/6—1(2)2m+1/3的相反数=2—5m—1/4(2m+1/3)的相反数=2—5m—1/4
(1)x—1/2=2x+1/6—1
(2)2m+1/3的相反数=2—5m—1/4
(2m+1/3)的相反数=2—5m—1/4
(1)x—1/2=2x+1/6—1(2)2m+1/3的相反数=2—5m—1/4(2m+1/3)的相反数=2—5m—1/4
x-1/2=2x+1/6-1 x-1/2-x=2x+1/6-1-x -1/2=x-5/6 x=5/6-1/2=5/6-3/6=2/6=1/3
1/3的相反数是-1/3
得:2m-1/3=2-5m-1/4 2m-1/3+5m=2-5m-1/4+5m 7m-1/3=2-1/4 7m=2-1/4+1/3
7m=7/4+1/3=21/12+4/12=25/12 m=25/84
1、x-2x=1/6-1+1/2
x=1/3
2、
(1)1/3的相反数是-1/3 2m-1/3=2-5m-1/4
2m-1/3+5m=2-5m-1/4+5m
7m-1/3=2-1/4
7m=2-1/4+1/3
7m=7/4+1/3=21/12+4/12=25/12
m=25/84
(2)2m...
全部展开
1、x-2x=1/6-1+1/2
x=1/3
2、
(1)1/3的相反数是-1/3 2m-1/3=2-5m-1/4
2m-1/3+5m=2-5m-1/4+5m
7m-1/3=2-1/4
7m=2-1/4+1/3
7m=7/4+1/3=21/12+4/12=25/12
m=25/84
(2)2m+1/3的相反数是-2m-1/3
-(2m+1/3)=2-5m-1/4
-2m-1/3=2-5m-1/4
-2m+5m=2-1/4+1/3
3m=23/24
m=23/72
收起
x—1/2=2x+1/6—1
x-1/2+1/2=2x+1/6—1+1/2
x-2x=2x-2x+1/6—1+1/2
-x=-2/6
x=1/3
(2m+1/3)的相反数=2—5m—1/4
(2m+1/3)的相反数是-(2m+1/3)那么
-(2m+1/3)=2—5m—1/4
-...
全部展开
x—1/2=2x+1/6—1
x-1/2+1/2=2x+1/6—1+1/2
x-2x=2x-2x+1/6—1+1/2
-x=-2/6
x=1/3
(2m+1/3)的相反数=2—5m—1/4
(2m+1/3)的相反数是-(2m+1/3)那么
-(2m+1/3)=2—5m—1/4
-2m-1/3=2—5m—1/4
-2m+5m-1/3+1/3=2—5m+5m—1/4+1/3
3m=2—1/4+1/3
m=25/36
2m+1/3的相反数=2—5m—1/4
1/3的相反数是-1/3
得:2m-1/3=2-5m-1/4
2m+5m=2-1/4+1/3
7m=25/12
m=25/84
收起